Mathematical Understanding Concepts Ability in QR Code-Assisted Problem Solving by Gender - Faradillah , Ayu; Rizkia , Putri Awalia (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Students must be able to develop an accurate understanding of mathematical concepts since it is essential for them to understand the concepts related to their studies. The purpose of this study is to analyze the ability of students' conceptual understanding assisted by QR codes in solving mathematical problems based on gender. This study is a qualitative research project with a descriptive approach. The data collection techniques used in this study include tests, interviews, and documentation The subjects of this research were one male and one female students in one of the public high schools in Jakarta. The research findings indicate that both male and female students perform equally well in the indicators of restating concepts and providing examples and non-examples of the material taught. Subsequently, the male student is great in presenting concepts related to the learned material through mathematical representations. On the other hand, the female student is great in applying concepts logically. However, both male and female students still exhibit deficiencies in their ability to classify objects based on the concepts that have been taught.